A New Species of Ant Belonging to the Pheidole Pilifera Complex (Hymenoptera: Formicidae) - Robert E. Gregg (Psyche: A Journal of Entomology)
A small collection of ants representing the genus Pheidole from several localities in Western United States was given to me recently by Dr. W. S. Creighton. Among these specimens are samples of several colonies from Oregon which prove to be a new species. The description of this ant follows herewith